Tubular carbon nanomaterial and preparation method thereof, composite coating and coating product

By preparing low-cost tubular carbon nanomaterials and combining components such as aqueous epoxy resins, the problems of high cost and insufficient performance of carbon nanotubes in the prior art are solved, and high-performance coating products are realized, satisfying coating products Durability and corrosion resistance requirements.

CN119218979APending Publication Date: 2024-12-31ZHANJIANG POWER SUPPLY BUREAU OF GUANGDONG POWER GRID CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411461985.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The cost of carbon nanotubes in the prior art is high and cannot meet the anti-corrosion requirements in special environments, resulting in poor application economy and insufficient performance in the field of metal anti-corrosion.

Method used

Provide a method for preparing tubular carbon nanomaterials, by mixing, drying, heat-treating and pickling the nanorod material with a carbon source in a solvent, and preparing low-cost and excellent performance tubular carbon nanomaterials for replacement of commercial carbon nanometers. The composite coating is prepared by combining aqueous epoxy resin, curing agent, zinc powder, defoaming agent and film forming additives to improve the adhesion, impact resistance and electrochemical impedance of the coating.

Benefits of technology

It has achieved the reduction of coating costs, improved coating protection performance, met the durability and corrosion resistance requirements of coated products, and has excellent adhesion, impact resistance and high electrochemical impedance value, while reducing corrosion current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a tubular carbon nanomaterial and a preparation method thereof, a composite coating and a coating product. The preparation method of the tubular carbon nanomaterial comprises the following steps: mixing a nanorod material and a carbon source in a solvent, and drying to obtain a precursor; carrying out heat treatment on the precursor in protective gas to obtain a carbon-coated nanorod; and carrying out acid pickling on the carbon-coated nanorod to remove the nanorod material, so as to obtain the tubular carbon nanomaterial. The preparation method comprises the following steps: firstly, mixing a nanorod material and a carbon source solution, and drying to obtain a precursor; carrying out heat treatment on the precursor in protective gas, so that the carbon source can be uniformly coated on the surface of the nanorod material to obtain a carbon-coated nanorod; and finally, carrying out acid pickling on the carbon-coated nanorod to remove the nanorod material, so as to obtain the tubular carbon nanomaterial. The preparation method is simple in process and relatively low in cost, and the tubular carbon nanomaterial is used for replacing a commercial carbon nanotube in a coating, so that the coating has good protection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and in particular to a tubular carbon nanomaterial and a preparation method thereof, a composite coating and a coating product. Background Art

[0002] Carbon nanotubes have the characteristics of large specific surface area, strong thermal stability, excellent mechanical properties, etc. When used as coating nano-additives, they can form a dense, corrosion-resistant film layer on the substrate and have good adhesion to metal and alloy materials. Therefore, they have important applications and broad prospects in the field of metal corrosion protection.

[0003] Studies have reported that the introduction of carbon nanotubes into epoxy zinc-rich paint can significantly improve the anti-corrosion performance of the coating, and at the same time can reduce the amount of zinc powder used and reduce the weight of the coating. However, the cost of carbon nanotubes in the prior art is relatively high, the economic efficiency is poor, and it cannot meet the anti-corrosion requirements in special environments.

[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0005] Based on this, the present application provides a method for preparing a tubular carbon nanomaterial. The preparation method has a simple process and low cost, can effectively reduce the cost of coatings, and enables the coatings to have good protective properties; and accordingly provides a tubular carbon nanomaterial, a composite coating and a coating product.

[0006] The specific technical solutions are as follows:

[0007] In a first aspect of the present application, a method for preparing a tubular nanomaterial is provided, comprising the following steps:

[0008] The nanorod material and the carbon source are mixed in a solvent and dried to obtain a precursor;

[0009] In a protective gas, the precursor is subjected to a heat treatment to obtain carbon-coated nanorods;

[0010] The carbon-coated nanorods are acid-washed to remove the nanorod material, thereby obtaining the tubular carbon nanomaterial.

[0011] The preparation method of the tubular carbon nanomaterial of the present application firstly mixes the nanorod material and the carbon source solution, and obtains a precursor after drying; then the precursor is heat-treated in a protective gas, and the carbon source can be relatively evenly coated on the surface of the nanorod material to obtain a carbon-coated nanorod; finally, the carbon-coated nanorod is acid-washed to remove the nanorod material, and the tubular carbon nanomaterial is obtained. The preparation method is simple in process and low in cost. The tubular carbon nanomaterial is used in coatings instead of commercial carbon nanotubes, which can make the coating have good protective properties.

[0012] In some of the embodiments, the mass ratio of the carbon source to the nanorod material is 0.5:1 to 2:1.

[0013] In some embodiments, the mass ratio of the carbon source to the nanorod material is 1-2:1.

[0014] In some embodiments, the nanorod material is selected from at least one of titanium dioxide nanorods, zinc oxide nanorods, attapulgite and sepiolite;

[0015] and / or, the carbon source is selected from at least one of glucose, fructose, sucrose, chitosan, maltose and tetrahydrofuranol;

[0016] And / or, the acid used for pickling is selected from at least one of H2SO4, HF, HCl and HNO3.

[0017] In some embodiments, the heat treatment is performed at a temperature of 600° C. to 800° C. and for a time of 2 h to 5 h.

[0018] In a second aspect of the present application, a tubular nanomaterial is provided. The tubular nanomaterial is prepared by the method for preparing the tubular nanomaterial.

[0019] In a third aspect of the present application, a composite coating is provided, comprising the following components in parts by weight:

[0020] 15-35 parts of waterborne epoxy resin;

[0021] 2~8 parts of curing agent;

[0022] Zinc powder 60~80 parts;

[0023] 0.2 to 1.2 parts of the above-mentioned tubular carbon nanomaterial;

[0024] Defoaming agent 0.2~0.8 parts;

[0025] 5~10 parts of film-forming aid.

[0026] The above-mentioned composite coating combines the tubular carbon nanomaterial of the present application with a water-based epoxy resin, a curing agent, zinc powder, a defoaming agent and a film-forming aid. By controlling the specific ratio of each preparation raw material, the components work synergistically, which promotes the addition of the tubular carbon nanomaterial. While improving the adhesion, impact resistance and high electrochemical impedance value of the composite coating, it reduces the corrosion current density, so that it can meet the durability and corrosion resistance requirements of the coated product.

[0027] In some embodiments, the following components are included by weight:

[0028] 15-25 parts of waterborne epoxy resin;

[0029] 2~8 parts of curing agent;

[0030] Zinc powder 60~80 parts;

[0031] 0.2 to 0.6 parts of the above-mentioned tubular carbon nanomaterial;

[0032] Defoaming agent 0.2~0.8 parts;

[0033] 5~10 parts of film-forming aid.

[0034] In some embodiments, the curing agent includes at least one of an aromatic amine, an aliphatic amine, and a polyamide;

[0035] and / or, the defoaming agent comprises at least one of BYK 011, BYK 024 and BYK 028;

[0036] And / or, the film-forming aid includes at least one of propylene glycol methyl ether, propylene glycol butyl ether, ethylene glycol butyl ether and isopropyl alcohol.

[0037] The fourth aspect of the present application also provides a coated product, comprising a coating obtained by curing the above-mentioned composite coating. DETAILED DESCRIPTION

[0038] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0039] The implementation of this application is described in detail below in combination with some implementation methods and examples. This example is implemented based on the technical solution of this application, and provides a detailed implementation method and specific operation process, but the protection scope of this application is not limited to the following examples.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0041] the term

[0042] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0043] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0044] In the present application, the terms "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0045] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0046] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0047] In this application, unless otherwise specified, the temperature parameter is allowed to be either a constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0048] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 2~5h means that the units of the left endpoint "2" and the right endpoint "5" are both h (hours).

[0049] An embodiment of the present application provides a method for preparing a tubular carbon nanomaterial, comprising steps a to c.

[0050] Step a: Mix the nanorod material and the carbon source solution, and dry them to obtain a precursor.

[0051] In some embodiments, the mass ratio of the carbon source to the nanorod material is 0.5:1-2:1.

[0052] The mass ratio of the carbon source to the nanorod material is in the range of "0.5:1-2:1", that is, the minimum and maximum values ​​in the range of 0.5:1-2:1, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1; or a range consisting of any two of these values, including, as an example, 1:1-2:1.

[0053] In some embodiments, the mass ratio of the carbon source to the nanorod material is 1:1 to 2:1.

[0054] By further controlling the mass ratio of the carbon source and the nanorod material within the above-mentioned ratio range, the carbon source can be more evenly coated on the surface of the nanorod material, and the adhesion and anti-corrosion comprehensive performance of the composite coating are better.

[0055] In some embodiments, the nanorod material is selected from at least one of titanium dioxide nanorods, zinc oxide nanorods, attapulgite and sepiolite.

[0056] In some embodiments, the carbon source is selected from at least one of glucose, fructose, sucrose, chitosan, maltose and tetrahydrofuranol.

[0057] It is understandable that by selecting different small molecule organic carbon sources and regulating the preparation process, different functional groups such as hydroxyl, carboxyl, amino, etc. can be introduced on the surface of carbon nanotubes, thereby achieving the regulation of their surface chemical properties. This enables carbon nanotubes to better combine or interact with other materials, expanding their applications in composite coating preparation, surface modification, etc. Small molecule organic carbon sources are widely available and relatively cheap, which makes the cost of this preparation method relatively low, which is conducive to large-scale production and application. Compared with some complex and costly nanomaterial preparation methods, it has obvious economic advantages.

[0058] In some embodiments, the drying method is spray drying or evaporating the solvent under stirring conditions.

[0059] Specifically, the drying is to evaporate the solvent under magnetic stirring in a water bath at 60°C to 100°C.

[0060] Step b: heat-treating the above precursor in a protective gas to obtain carbon-coated nanorods.

[0061] In some embodiments, the protective gas is nitrogen or argon.

[0062] In some embodiments, the heat treatment temperature is 600°C-800°C.

[0063] In some embodiments, the heat treatment time is 2h~5h.

[0064] It is understandable that the preparation process of this method is relatively flexible and can be adjusted and optimized according to different needs and conditions. For example, the structure and performance of carbon nanotubes can be regulated by changing the temperature, time, atmosphere and other parameters of the heat treatment; different templates and methods of removing templates can also be selected to adapt to different application scenarios.

[0065] Step c: acid-washing the carbon-coated nanorods to remove the nanorod materials and obtain tubular carbon nanomaterials.

[0066] In the above-mentioned preparation method of tubular carbon nanomaterials, small molecule organic carbon sources can be more evenly coated on the surface of nanorod-shaped materials. By controlling the reaction conditions and the amount of carbon source, etc., the parameters such as the diameter, length, and wall thickness of the tubular carbon nanomaterials can be regulated, thereby obtaining nanotubes with suitable size and structure to meet the needs of different application scenarios.

[0067] In some embodiments, the acid is selected from at least one of H2SO4, HF, HCl and HNO3.

[0068] The preparation method of the tubular carbon nanomaterial of the present application firstly mixes the nanorod material and the carbon source solution, and obtains a precursor after drying; then the precursor is heat-treated in a protective gas, and the carbon source can be relatively evenly coated on the surface of the nanorod material to obtain a carbon-coated nanorod; finally, the carbon-coated nanorod is acid-washed to remove the nanorod material, and the tubular carbon nanomaterial is obtained. The preparation method is simple in process and low in cost. The tubular carbon nanomaterial is used in coatings instead of commercial carbon nanotubes, which can make the coating have good protective properties.

[0069] An embodiment of the present application provides a composite coating, which includes the following components in parts by weight:

[0070] 15-25 parts of waterborne epoxy resin;

[0071] 2~8 parts of curing agent;

[0072] Zinc powder 60~80 parts;

[0073] 0.2 to 1.2 parts of the above tubular carbon nanomaterial;

[0074] Defoaming agent 0.2~0.8 parts;

[0075] 5~10 parts of film-forming aid.

[0076] It should be noted that the value range of waterborne epoxy resin is "15 parts to 35 parts", which means the minimum and maximum values ​​of the range of 15 parts to 35 parts, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and the following point values: 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts; or a range composed of any two of these values, as an example, including: 20 parts to 30 parts.

[0077] The value range of the curing agent is "2 parts to 8 parts", that is, the minimum and maximum values ​​of the range of 2 parts to 8 parts, and every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts or 8 parts; or a range composed of any two of these values, as an example, including: 3 parts to 5 parts.

[0078] The value range of zinc powder is "60 parts to 80 parts", that is, the minimum and maximum values ​​of the range of 60 parts to 80 parts, and every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts or 80 parts; or a range composed of any two of these values, as an example, including: 60 parts to 75 parts.

[0079] The value range of the tubular carbon nanomaterial is "0.2 parts to 1.2 parts", that is, the minimum and maximum values ​​of the range of 0.2 parts to 1.2 parts, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts or 1.2 parts; or a range composed of any two of these values, as an example, including: 0.2 parts to 1 part.

[0080] The value range of the defoaming agent is "0.2 parts to 0.8 parts", that is, the minimum and maximum values ​​of the range of 0.2 parts to 0.8 parts, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts or 0.8 parts; or a range composed of any two of these values, as an example, including: 0.2 parts to 0.6 parts.

[0081] The range of the film-forming aid is "5 parts to 10 parts", which means the minimum and maximum values ​​of the range of 5 parts to 10 parts, and every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts or 10 parts; or a range consisting of any two of these values, including, as an example, 5 parts to 8 parts.

[0082] The above-mentioned composite coating combines the tubular carbon nanomaterial of the present application with a water-based epoxy resin, a curing agent, zinc powder, a defoaming agent and a film-forming aid. By controlling the specific ratio of each preparation raw material, the components work synergistically, which promotes the addition of the tubular carbon nanomaterial. While improving the adhesion, impact resistance and high electrochemical impedance value of the composite coating, it reduces the corrosion current density, so that it can meet the durability and corrosion resistance requirements of the coated product.

[0083] In some embodiments, the following components are included by weight:

[0084] 15-25 parts of waterborne epoxy resin;

[0085] 2~8 parts of curing agent;

[0086] Zinc powder 60~80 parts;

[0087] 0.2 to 0.6 parts of tubular carbon nanomaterials;

[0088] Defoaming agent 0.2~0.8 parts;

[0089] 5~10 parts of film-forming aid.

[0090] By further controlling the ratio range of the prepared raw materials, the adhesion, impact resistance and electrochemical impedance value of the composite coating are better, and at the same time, it has a lower corrosion current density.

[0091] In some embodiments, the curing agent includes at least one of aromatic amine, aliphatic amine and polyamide.

[0092] In some embodiments, the defoaming agent includes at least one of BYK 011, BYK 024 and BYK 028.

[0093] In some embodiments, the film-forming aid includes at least one of propylene glycol methyl ether, propylene glycol butyl ether, ethylene glycol butyl ether and isopropyl alcohol.

[0094] Another embodiment of the present application also provides a method for preparing a composite coating, comprising mixing the raw materials for preparing the composite coating to prepare the composite coating.

[0095] Specifically, it includes step S10 to step S20.

[0096] Step S10: Mixing the waterborne epoxy resin, the zinc powder, the tubular carbon nanomaterial, the defoamer, the film-forming aid and the solvent to prepare a premixed slurry.

[0097] Step S20: Add a curing agent to the premixed slurry to prepare a composite coating; the composite coating comprises the following components in parts by weight:

[0098] 15-25 parts of waterborne epoxy resin;

[0099] 2~8 parts of curing agent;

[0100] Zinc powder 60~80 parts;

[0101] 0.2 to 1.2 parts of the above tubular carbon nanomaterial;

[0102] Defoaming agent 0.2~0.8 parts;

[0103] 5~10 parts of film-forming aid.

[0104] The composite coating preparation method is simple to operate, and the prepared composite coating has excellent adhesion, impact resistance, and a high electrochemical impedance value, as well as a low corrosion current density.

[0105] One embodiment of the present application is the use of the above-mentioned composite coating in the preparation of coated products.

[0106] One embodiment of the present application also provides a coating product, including a coating obtained by curing the composite coating prepared by the above composite coating or the above composite coating preparation method.

[0107] The coating product provided by the present application has better corrosion resistance.

[0108] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0109] In order to better illustrate the present application, the contents of the present application are further described below in conjunction with embodiments.

[0110] Example 1

[0111] (1) Provide the following raw materials by weight: 30 parts of waterborne epoxy resin, 5.6 parts of curing agent, 60 parts of zinc powder, 0.2 parts of tubular carbon nanomaterials, 0.4 parts of defoaming agent and 8 parts of film-forming aid. For details, please refer to Table 1.

[0112] The water-based epoxy resin model is ER2153, which comes from Guangzhou Jinghao New Materials Co., Ltd.; the curing agent is aliphatic amine, model AMH1180, which comes from Guangzhou Jinghao New Materials Co., Ltd.; the zinc powder comes from Shenlong Zinc Co., Ltd.; the defoamer model is BYK 024, which comes from BYK Chemical Additives Co., Ltd.; and the film-forming additives are propylene glycol methyl ether and propylene glycol butyl ether, which come from Koloman Chemical Co., Ltd.

[0113] (2) 30 parts of waterborne epoxy resin with an epoxy equivalent of 600-800 g / eq, 4 parts of propylene glycol methyl ether, 4 parts of propylene glycol butyl ether, 0.4 parts of BYK346, 60 parts of zinc powder, and 0.2 parts of tubular carbon nanomaterials were sequentially added into a disperser and dispersed at high speed through cooling water to obtain a premixed slurry.

[0114] The preparation method of the tubular carbon nanomaterial is as follows: 5g of rod-shaped zinc oxide and 5g of small molecule sucrose are mixed with water, and then placed in a water bath at 80°C with magnetic stirring until the water evaporates to obtain a precursor. The precursor is placed in a tubular furnace and heat-treated at 800°C for 3h under an inert atmosphere to obtain carbon-coated zinc oxide. The tubular carbon nanomaterial can be obtained by removing the template with HCl.

[0115] (3) 5.6 parts of a water-based amine curing agent having an amine value of 150 g / eq was added to the premixed slurry and dispersed at high speed to prepare an epoxy zinc-rich coating.

[0116] (4) Spray the epoxy zinc-rich coating onto Q235 steel plates to prepare 50-60 μm thick steel plates. The corrosion resistance of the coatings was quickly evaluated by measuring the impedance value, corrosion current, and corrosion current density of the electrical impedance spectroscopy (EIS).

[0117] Embodiment 2-3

[0118] The preparation methods of the composite coatings in Examples 2 to 3 are basically the same as those in Example 1, except that the mass ratios of the carbon source and the nanorod material in the preparation method of the tubular carbon nanomaterial are different, as shown in Table 1.

[0119] The other steps and conditions are the same as those in Example 1.

[0120] Embodiments 4 to 7

[0121] The preparation methods of the composite coatings in Examples 4 to 7 are substantially the same as those in Example 2, except that the ratios of the raw materials in Table 1 are different. Please see Table 1 for details.

[0122] The other steps and conditions are the same as those in Example 1.

[0123] Comparative Example 1

[0124] The preparation method of the composite coating in Comparative Example 1 is basically the same as that in Example 1, except that the preparation raw materials in Table 1 are different and no tubular carbon nanomaterial is introduced. The specific steps are as follows:

[0125] (1) The following raw materials are provided in parts by weight: 30 parts of waterborne epoxy resin, 5.6 parts of curing agent, 60 parts of zinc powder, 0.2 parts of tubular carbon nanomaterials, 0.4 parts of defoaming agent and 8 parts of film-forming aid.

[0126] (2) 30 parts of waterborne epoxy resin with an epoxy equivalent of 600-800 g / eq, 4 parts of propylene glycol methyl ether, 4 parts of propylene glycol butyl ether, 0.4 parts of BYK346, and 60 parts of zinc powder were sequentially added into a disperser and dispersed at high speed through cooling water to obtain a premixed slurry.

[0127] (3) 5.6 parts of a water-based amine curing agent having an amine value of 150 g / eq was added to the premixed slurry and dispersed at high speed to prepare an epoxy zinc-rich coating.

[0128] (4) Spray the epoxy zinc-rich coating onto Q235 steel plates to prepare 50-60 μm thick steel plates. The corrosion resistance of the coatings was quickly evaluated by measuring the impedance value, corrosion current, and corrosion current density of the electrical impedance spectroscopy (EIS).

[0129] Comparative Example 2

[0130] The preparation method of the composite coating in Comparative Example 2 is basically the same as that in Example 1, except that the preparation raw materials in Table 1 are different, and a commercial carbon nanotube material (model YSKC-30, purchased from Dongguan Yushuo New Material Technology Co., Ltd.) is introduced. The specific steps are as follows:

[0131] (1) The following raw materials are provided in parts by weight: 30 parts of waterborne epoxy resin, 5.6 parts of curing agent, 60 parts of zinc powder, 0.2 parts of tubular carbon nanomaterials, 0.4 parts of defoaming agent and 8 parts of film-forming aid.

[0132] (2) 30 parts of water-based epoxy resin with an epoxy equivalent of 600-800 g / eq, 4 parts of propylene glycol methyl ether, 4 parts of propylene glycol butyl ether, 0.4 parts of BYK346, 60 parts of zinc powder, and 0.2 parts of carbon nanotube material are sequentially added into a disperser and dispersed at high speed through cooling water to obtain a premixed slurry.

[0133] (3) 5.6 parts of a water-based amine curing agent having an amine value of 150 g / eq was added to the premixed slurry and dispersed at high speed to prepare an epoxy zinc-rich coating.

[0134] (4) Spray the epoxy zinc-rich coating onto Q235 steel plates to prepare 50-60 μm thick steel plates. The corrosion resistance of the coatings was quickly evaluated by measuring the impedance value, corrosion current, and corrosion current density of the electrical impedance spectroscopy (EIS).

[0135] Comparative Examples 2~3

[0136] The preparation methods of the composite coatings in Comparative Examples 2-3 are basically the same as those in Example 1, except that the amounts of raw materials used in preparing the composite coatings are different, as shown in Table 1.

[0137] The remaining steps and conditions are the same as those in Example 1.

[0138] The following is a performance test.

[0139] The composite coating products prepared in the above-mentioned specific examples 1 to 7 and comparative examples 1 to 2 were subjected to the following tests:

[0140] 1. Adhesion test

[0141] Specifically implement the requirements of GB / T 5210-2006 standard.

[0142] 2. Impact resistance test

[0143] Specifically implement the requirements of GB / T 1732-2020 standard.

[0144] 3. Salt spray resistance test

[0145] Specific implementation of GB / T1771-91 standard requirements.

[0146] 4. Electrochemical impedance test

[0147] Specifically implement the requirements of GB / T 39482.1-2023 standard.

[0148] 5. Corrosion current test

[0149] Specifically implement the requirements of GB / T 40299-2021 standard.

[0150] Table 1

[0151]

[0152] Note: “ / ” indicates that the component does not exist.

[0153] Comparative analysis of the test data of Examples 1 to 7 and Comparative Examples 1 to 2 in Table 1 shows that: in Comparative Example 1, carbon nanotubes and tubular carbon nanomaterials are not added, and the mechanical properties, salt spray resistance and electrochemical properties of the prepared epoxy zinc-rich paint are relatively poor. After adding commercial carbon nanotube materials to Comparative Example 2, the salt spray resistance time is increased by 0.5 times, and the electrical properties are improved by two orders of magnitude. The effect of the ratio of organic carbon source and nanorod material on the performance of one-dimensional tubular materials is explored in the embodiment. From the data, the tubular material prepared by 0.5:1 has little improvement on the performance of epoxy zinc-rich primer, and the improvement of tubular nanomaterials prepared by the two ratios of 1:1 and 1:2 is roughly the same. Therefore, in order to save costs, it is more appropriate to select a coating ratio of 1:1. Examples 2 / 4 / 5 respectively study the effect of the amount of tubular carbon nanomaterial added on the performance of epoxy zinc-rich primer. It can be seen from Table 1 that the amount of addition in Example 4 is the most appropriate. The reason why tubular carbon nanomaterials improve the performance of epoxy zinc-rich primer is mainly that the nanomaterials cross-link the paint films to form a dense network, thereby improving the adhesion and impact resistance of the coating, increasing the electrochemical impedance value, and reducing the corrosion current density.

[0154] In summary, the composite coating of the present application has excellent adhesion, impact resistance and high electrochemical impedance value, and at the same time has low corrosion current density, which can meet the practical application of coated products.

[0155] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0156] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A method for preparing a tubular carbon nanomaterial, characterized in that: The steps include: The nanorod material and the carbon source are mixed in a solvent and dried to obtain a precursor; In a protective gas, the precursor is subjected to a heat treatment to obtain carbon-coated nanorods; The carbon-coated nanorods are acid-washed to remove the nanorod material, thereby obtaining the tubular carbon nanomaterial.

2. The method for preparing the tubular carbon nanomaterial according to claim 1, characterized in that: The mass ratio of the carbon source to the nanorod material is 0.5:1-2:

1.

3. The method for preparing the tubular carbon nanomaterial according to claim 2, characterized in that: The mass ratio of the carbon source to the nanorod material is 1-2:

1.

4. The method for preparing a tubular carbon nanomaterial according to any one of claims 1 to 3, characterized in that: The nanorod material is selected from at least one of titanium dioxide nanorods, zinc oxide nanorods, attapulgite and sepiolite; and / or, the carbon source is selected from at least one of glucose, fructose, sucrose, chitosan, maltose and tetrahydrofuranol; And / or, the acid used for pickling is selected from at least one of H2SO4, HF, HCl and HNO3.

5. The method for preparing a tubular carbon nanomaterial according to any one of claims 1 to 2, characterized in that: The heat treatment temperature is 600° C. to 800° C., and the time is 2 h to 5 h.

6. A tubular carbon nanomaterial, characterized in that: The tubular carbon nanomaterial is prepared by the method for preparing a tubular carbon nanomaterial according to any one of claims 1 to 5.

7. A composite coating, characterized in that: By weight, it includes the following components: 15-35 parts of waterborne epoxy resin; 2 to 8 parts of curing agent; Zinc powder 60~80 parts; 0.2 to 1.2 parts of the tubular carbon nanomaterial according to claim 6; Defoaming agent 0.2~0.8 parts; 5~10 parts of film-forming aid.

8. The composite coating according to claim 7, characterized in that: By weight, it includes the following components: 15-25 parts of waterborne epoxy resin; 2 to 8 parts of curing agent; Zinc powder 60~80 parts; 0.2 to 0.6 parts of the tubular carbon nanomaterial according to claim 6; Defoaming agent 0.2~0.8 parts; 5~10 parts of film-forming aid.

9. The composite coating according to claim 7 or 8, characterized in that: The curing agent includes at least one of aromatic amine, aliphatic amine and polyamide; and / or, the defoaming agent comprises at least one of BYK 011, BYK 024 and BYK 028; And / or, the film-forming aid includes at least one of propylene glycol methyl ether, propylene glycol butyl ether, ethylene glycol butyl ether and isopropyl alcohol.

10. A coated product, characterized in that: The invention comprises a coating obtained by curing the composite coating according to any one of claims 7 to 9.